Flow Augmentation in Acute Ischemic Stroke. (January 2016) - Yadollahikhales, Golnaz; Borhani-Haghighi, Afshin; Torabi-Nami, Mohammad; Edgell, Randall; Cruz-Flores, Salvador
There is an urgent need for additional therapeutic options for acute ischemic stroke considering the major pitfalls of the options available. Herein, we briefly review the role of cerebral blood flow, collaterals, vasoreactivity, and reperfusion injury in acute ischemic stroke. Then, we reviewed pharmacological and interventional measures such as volume expansion and induced hypertension, intra-aortic balloon counterpulsation, partial aortic occlusion, extracranial–intracranial carotid bypass surgery, sphenopalatine ganglion stimulation, and transcranial laser therapy with regard to their effects on flow augmentation and neuroprotection.